Evidence of a solvent screen effect affecting the redox properties of Co(II) ions in CoAPO-37, CoAPO-40 and CoIST-2 (AEN), by cyclic voltammetry - Gabelica, Z. (2012)
Cyclic voltammetric experiments of framework Co(II) ions in three different CoAPO structures have provided evidence for a screening effect created by solvent or template molecules which results in a facile oxidation (and a difficult reduction) of the Co(II) ions incorporated into the most open (the less strained) structures. An apparent contradiction of these findings with respect to theoretical expectations is discussed.